The Role of Job Satisfaction in Mediating the Influence of Organizational Justice on Organizational Citizenship Behavior - Jufrizen Jufrizen; Ami Kumala Sari (CERED Indonesia Institute, 2023)
The research aims to analyze several things, namely the influence of organizational justice on organizational citizenship behavior, the influence of organizational justice on job satisfaction, the influence of job satisfaction on organizational citizenship behavior, and the influence of organizational justice on organizational citizenship behavior through job satisfaction. This research uses associative research with 114 respondents who are employees at PT Pelabuhan Indonesia (Persero) Regional 1 Belawan Branch. The data collection technique uses a list of statements, such as a questionnaire, and the data analysis technique uses Path Analysis to test the four hypotheses proposed in this research using the Partial Least Square (SmartPls) application. The research results show that the influence of organizational justice on organizational citizenship behavior is positive and significant, the influence of organizational justice on job satisfaction is positive and significant, the influence of job satisfaction on organizational citizenship behavior is positive and significant, the influence of organizational justice on organizational citizenship behavior through job satisfaction is positive and significant ( meaning that job satisfaction mediates the influence of organizational justice on organizational citizenship behavior).